On Functions of Several Split-Quaternionic Variables - Gueo Grantcharov; Camilo Montoya (Advances in Mathematical Physics)
Alesker studied a relation between the determinant of a quaternionic Hessian of a function and a specific complex volume form. In this note we show that similar relation holds for functions of several split-quaternionic variables and point to some relations with geometry.